Anti-inflammatory effect of Mitragyna speciosa crude methanol extract on the guinea pig ileum. - Shaik Mossadeq, Wan Mastura; Khalid, Syamimi; M.P, Azyyati; Z.A., Zakaria; Abdul Kadir, Arifah; Rajion, Mohamed Ali; M Taufik, Hidayat; M.L., Jabit; M. R., Sulaiman (Georg Thieme Verlag, 2009)
In a recent study, we have shown that the crude methanol extract of Mitragyna speciosa (of the family Rubiaceae) exerted significant in vivo anti-inflammatory activities in rodents as evident in the carageenan-induced paw edema and cotton pellet-induced granuloma tests [1], but the underlying mechanism is poorly understood. Our present study aims to explore the anti-inflammatory activities of this plant in vitro in order to rationalize the traditional use of this plant in the treatment of some stomach ailments [2]. The pharmacologic actions of M. speciosa were assessed by measuring the mechanical activity of isolated guinea pig ileum strips in an organ bath. The resultant methanol extract (0.01–0.05mg/ml) caused a stimulatory effect followed by a relaxation of ileal activities at a higher dose (0.3–5mg/ml) (p<0.05). These results indicate that M. speciosa exert spasmogenic effects at a lower dose and a spasmolytic effect at a higher dose thus corroborating the use of plant in the treatment of diarrhoea and constipation. Moreover, results indicated that pretreatment with M. speciosa (0.3–5mg/ml) which were tested positive for flavonoids, alkaloids, saponins, sterols and tannins produced significant concentration-dependant inhibition of spasmogenic activities when exposed to single submaximal contraction induced by histamine (H) and bradykinin (B). These results suggest that the anti-inflammatory activity of M. speciosa is mediated possibly through the H and B receptor antagonism, thus providing a scientific basis for the folkloric use of this plant in stomach disorders.